Educator Examines Tools to Engage Communities in Classrooms - Samantha Basile (The University of Alabama, 2022)
Review of the book: Inviting Families into the Classroom: Learning from a Life in Teaching. Lynne Yermanock Strieb. Teachers College Press: New York, NY, 2010, 240 pages. ISBN 978-0-8077-5082-7